2010
DOI: 10.2175/193864710798158968
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Nitrification-Denitrification to Meet Low Effluent Nitrogen Limits: Modeling, Performance and Reliability

Abstract: Simultaneous nitrification-denitrification (SND) has been referred to as a biological process for nitrogen removal where nitrification and denitrification occur concurrently in the same aerobic reactor. SND facilities, investigated in this study, have been shown to remove 80 to 96 percent nitrogen without additional carbon and alkalinity. Carbon availability and bulk dissolved oxygen (DO) concentrations were found to be important process parameters for SND activity. Data suggest that a chemical oxygen demand-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…This would be anticipated since the amount of denitrification should be set by the availability of substrate (constant) and the bulk DO concentration in the reactor. Jimenez et al (2010) demonstrated that the structure of the ASDM model in the BioWin simulator (Barker and Dold, 1997) allowed the pilot plant performance to be calibrated reasonably well with minor adjustments to default parameters. The modeling results confirmed the earlier discussion about SND that the most sensitive parameters are the various halfsaturation constants, as noted by others (O'Shaugnessey et al, 1998;Insel et al, 2003 andMagbanaua et al, 2007), as well as the heterotroph maximum specific growth rate.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This would be anticipated since the amount of denitrification should be set by the availability of substrate (constant) and the bulk DO concentration in the reactor. Jimenez et al (2010) demonstrated that the structure of the ASDM model in the BioWin simulator (Barker and Dold, 1997) allowed the pilot plant performance to be calibrated reasonably well with minor adjustments to default parameters. The modeling results confirmed the earlier discussion about SND that the most sensitive parameters are the various halfsaturation constants, as noted by others (O'Shaugnessey et al, 1998;Insel et al, 2003 andMagbanaua et al, 2007), as well as the heterotroph maximum specific growth rate.…”
Section: Methodsmentioning
confidence: 99%
“…The results indicated that significant nitrogen removal could be realized through SND, and the two main factors affecting SND performance were organic carbon availability and operating DO concentration. Jimenez et al (2010) showed that the influent rbCOD:N ratio strongly influences denitrification in the SND process. Data suggest that an influent COD:N ratio of at least 10:1 is required to achieve near-complete denitrification through SND.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a further consideration is that simultaneous nitrification-denitrification (SND) can be expected when nitrifying at low DO concentration, and this may mask nitrite accumulation (Jimenez et al, 2010).…”
Section: Figure 3: Analysis Of Grab Samples From An A/o Process Demonmentioning
confidence: 99%